1992
DOI: 10.1111/j.1365-2710.1992.tb01278.x
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatographic determination of ciprofloxacin in plasma

Abstract: This paper describes an accurate, specific and sensitive high-performance liquid chromatographic (HPLC) method for the determination of ciprofloxacin in small samples (0.5 ml). The samples, after pretreatment by solvent extraction, were eluted on a reversed-phase column and detected by an ultraviolet detector. The results obtained on patient samples are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Ciprofloxacin concentrations were measured by means of a high-performance liquid chromatographic assay previously described [14]. Immediately after collection, each blood sample was gently reversed a few times to assure complete mixing with the anticoagulant and was centrifuged for 10 min, at approximately 1,000´g at 3°C to separate the plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Ciprofloxacin concentrations were measured by means of a high-performance liquid chromatographic assay previously described [14]. Immediately after collection, each blood sample was gently reversed a few times to assure complete mixing with the anticoagulant and was centrifuged for 10 min, at approximately 1,000´g at 3°C to separate the plasma.…”
Section: Methodsmentioning
confidence: 99%
“…It is also a common Tibetan medicine and has been used to treat stomach pain and blood disorders. In Mongolian medicine, the roots of S. lappa have been used to treat lung abscesses and phlegm [ 16 ]. Some eudesmane-, guaiane- and germacane-type sesquiterpenes have been isolated from S. lappa .…”
Section: Introductionmentioning
confidence: 99%
“…Some eudesmane-, guaiane- and germacane-type sesquiterpenes have been isolated from S. lappa . These compounds showed potential effects on chronic superficial gastritis, ulcer, cancer, bacterial, fungal and viral diseases [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is responsible for the negative super coiling of the bacterial DNA and consequently for its topological configuration, governing functions such as RNA transcription, protein synthesis, DNA replication and repair functions [2]. The literature survey revealed that variety of analytical methods reported for estimation of ciprofloxacin in human plasma and other biological fluids [3][4][5][6][7][8], spectrophotometry [9,10], HPLC [11][12][13], HPTLC [14], and spectrophotometric methods [15][16][17] have been reported for estimation of ornidazole alone as well as in combinations. RP-HPLC method was reported for estimation of Ciprofloxacin Hydrochloride and Ornidazole in Combined Pharmaceutical Dosage Form [18].…”
Section: Introductionmentioning
confidence: 99%